Clinical Research Involving Pregnant Women - Baylis, Françoise; Ballantyne, Angela (Research Ethics Forum, 2016)
This book discusses 'how' to respectfully and responsibly include pregnant women in clinical research. In sharp contrast, the existing literature predominantly focuses on the reasons 'why' the inclusion of pregnant women in clinical research is necessary - viz., to develop effective treatments for women during pregnancy, to promote fetal safety, to reduce harm to women and fetuses from suboptimal care, and to allow access to the benefits of research participation. This book supports the shift to a new default position, whereby pregnant women are included in clinical research unless researchers argue convincingly for their exclusion. This shift raises many as yet unexplored ethical and policy questions about existing barriers to the equitable inclusion of pregnant women in research. This book is original in three key ways. First, it presents an unparalleled depth of analysis of the ethics of research with pregnant women, bringing together many of the key authors in this field as well as experts in research ethics and in vulnerability who have not previously applied their work to pregnant women. Second, it includes innovative theoretical work in ethics and disease specific case studies that highlight the current complexity and future challenges of research involving pregnant women. Third, the book brings together authors who argue both for and against including more pregnant women in formal clinical trials. .